Społeczna odpowiedzialność przedsiębiorstw - państwo - społeczeństwo : przykład Wielkiej Brytanii i Francji - Łuszcz, Anna (Corporate Social Responsibility - Society - Country : France and Great Britain Example, 2009)
This article presents the impact of the political factors as well as the cultural-social factors on the character of Corporate Social Responsibility (CSR) in selected European countries. The interest was directed at the comparison of the concept development in France and in Great Britain due to the differences in the formation of these two types of countries, their legal systems and the social structures. However, it is also very important that both countries, which derive from the same civilization circle, are characterized by a similar level of material culture development and social institutions development, which made their comparison and analysis considerably easier. The specificity of the social factors, illustrated with an example of France and Great Britain, poses a question how political, social and economical differences influence the defining of the corporation's role and their socially responsible activities. The article indicates what way the relations between the country and the society - which are based on formal and informal principles, values and traditions - determine the level of the institutionalization of activities with socially responsible quality.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 72-82